Parametric Modeling and Real Time Remote Experimentation of a Reconfigurable Coupled Pendulum. (2018) - Rajpal, Rohit; Kant, Mohit; Kuchibhatla, Sai Aditya Raman; Gangadharan, K.V.
Abstract: This paper presents parametric modeling and real time remote experimentation of a reconfigurable coupled pendulum on a data flow visual programming platform – G Programming. The motivation behind creating the experiment was to make it virtually available for e-learning in the field of vibration analysis & diagnostics. The derived math models replicated the low frequency system dynamics and were used in simulations to highlight inherent system behaviour. Finally, experiment was conducted for various system configuration settings characterized by pre-set discrete lengths of the pendulums. Sensors and actuators used for the experimentation were integrated using LabVIEW. Smartphone and Cross-Platform Communication Toolkit (SCCT) was employed to establish communication between remote user and Master computer. The experiment highlighted bimodal dynamic behaviour of the system in individual and combined modes of vibration through an Internet based remote experimentation platform.